2004
DOI: 10.1097/01.asn.0000108522.79652.63
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous PDGF-D Is a Potent Mesangial Cell Mitogen and Causes a Severe Mesangial Proliferative Glomerulopathy

Abstract: Abstract. The PDGF family consists of at least four members, PDGF-A, -B, -C, and -D. All of the PDGF isoforms bind and signal through two known receptors, PDGF receptor-␣ and PDGF receptor-␤, which are constitutively expressed in the kidney and are upregulated in specific diseases. It is well established that PDGF-B plays a pivotal role in the mediation of glomerular mesangial cell proliferation. However, little is known of the roles of the recently discovered PDGF-C and -D in mediating renal injury. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 43 publications
5
51
0
Order By: Relevance
“…39 Mesangial proliferation induced by Flk-sel therapy was associated with alterations in expression of PDGF/ PDGFR, which are potent mitotic factors for mesangial cells. 40 This finding is consistent with previous report. 41 Notably, VEGF-A is capable of signaling through PDGFRs, 42 and so our VEGF-A mutant might directly stimulate PDGF pathways in our animals, leading to alterations in mesangial cell biology.…”
Section: Discussionsupporting
confidence: 93%
“…39 Mesangial proliferation induced by Flk-sel therapy was associated with alterations in expression of PDGF/ PDGFR, which are potent mitotic factors for mesangial cells. 40 This finding is consistent with previous report. 41 Notably, VEGF-A is capable of signaling through PDGFRs, 42 and so our VEGF-A mutant might directly stimulate PDGF pathways in our animals, leading to alterations in mesangial cell biology.…”
Section: Discussionsupporting
confidence: 93%
“…103 Mice with high circulating levels of PDGF-D after adenoviral transfection of the liver developed a severe mesangioproliferative glomerulopathy, characterized by enlarged glomeruli and a striking increase in glomerular cellularity. 104 Collectively, these data demonstrate potent roles of PDGF-B and -D in inducing mesangioproliferative changes as well as tubulointerstitial fibrosis in the case of PDGF-B.…”
Section: Overexpression or Pharmacologic Administrationmentioning
confidence: 90%
“…107 The induction of mesangioproliferative changes was reproduced in healthy mice and rats by hepatic transfection with viral constructs encoding PDGF-B, resulting in elevated circulating levels of this isoform. 104 Finally, glomerular overexpression of PDGF-B also drove bone marrow-derived cells toward a mesangial-like phenotype in vivo. 108 At very high dosages (5 mg/kg), PDGF-BB infusion into rats induced dosage-dependent renal tubulointerstitial cell proliferation, myofibroblast formation, and fibrosis, which were reversible after PDGF-BB infusion was abrogated.…”
Section: Overexpression or Pharmacologic Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16] It is well established that the PDGF-B and -D isoforms induce glomerular mesangial cell proliferation through engagement of the PDGFR-␤. [17][18][19][20] Furthermore, it has been shown that glomerular cell proliferation and extracellular matrix expansion in TSLP-transgenic (TSLP-Tg) mice are closely associated with enhanced expression of PDGF-B and PDGFR-␤. 21 These data indicate that the PDGF ligand/receptor system is an attractive therapeutic target to ameliorate the glomerular injury in the TSLP-Tg MPGN model.…”
mentioning
confidence: 99%